Theoretical model of hydrodynamic jet formation from accretion disks with turbulent viscosity - Arshilava, Erekle; Gogilashvili, M.; Loladze, V.; Jokhadze, I.; Modrekiladze, B.; Shatashvili, N. L.; Tevzadze, A. G. (Journal of high energy astrophysics, 2019)
We develop the theoretical model for the analytic description of hydrodynamic jets from protostellar disks employing the Beltrami-Bernoulli flow configuration of disk-jet structure. For this purpose we extend the standard turbulent viscosity prescription and derive several classes of analytic solutions using the flow parametrization in self-similar variables. Derived solutions describe the disk-jet structure, where for the first time jet properties are analytically linked with the properties of the accretion disk flow. The ratio of the jet ejection and disk accretion velocities is controlled by the turbulence parameter, while the ejection velocity increases with the decrease of local sound velocity and the jet launching radius. Derived solutions can be used to analyze the astrophysical jets from protostellar accretion disks and link the properties of outflows with the local observational properties of accretion disk flows.
Gesehen am 04.12.2019